MRA and ASL perfusion findings in pediatric reversible cerebral vasoconstriction syndrome - Kayfan, Samar (Radiol Case Rep, 2019)
Reversible vasoconstriction is rare in the pediatric population. Typically manifesting as peripheral vasoconstriction with variable neurologic symptoms, Reversible cerebral vasoconstriction syndrome is often a diagnosis of exclusion and may not be diagnosed in the absence of angiographic imaging. Shown here are 2 cases of pediatric Reversible cerebral vasoconstriction syndrome with disparate MRI findings and arterial spin labeling perfusion findings.